Culture in prison, culture on the street: the convergence between the convict code and code of the street. Issue 2 (15th March 2021) - Mitchell, Meghan M.; Pyrooz, David C.; Decker, Scott H.
ABSTRACT: The convict code guides behaviors, beliefs, and interactions of incarcerated people by encouraging them to mind their own business, never back down, keep to themselves, and not get too close with correctional officers. Within communities, a similar subculture exists, termed the code of the street, which values respect, toughness, autonomy, and anti-police sentiments. Despite the overlap in their themes, these cultures have been theorized and analyzed independently. Yet, with 600, 000 people entering and leaving prisons annually, it is possible that these seemingly distinct cultures blend together through the transition of people into and out of prison, raising theoretical and empirical questions about their independence. We examine the overlap between the convict code and code of the street in a representative sample of prisoners. Our results indicate that the code of the street and convict code are moderately correlated ( r = 0.368 to r = 0.591), although the code of the street indicator overlaps mainly with the convict code dimension for masculinity. A sizeable group (47%) of individuals held converging beliefs regarding these two constructs. Convergence was explained primarily by years in prison, prison misconduct, gang membership, and neighborhood quality. Implications for an integrated model of culture are discussed.